EFFECT OF FAMILY ENVIRONMENT AND STUDENT LEARNING MOTIVATION TO ACCOUNTING STUDENT LEARNING OUTCOMES CLASS X SMK 1 SOLOK SOUTH STATE - Jamil, Husnan; Arza, Fefri Indra; Jolianis, Jolianis (Pendidikan Ekonomi, 2013)
Abstract The research was conducted at SMK Negeri 1 South Solok the influence of family environment and students motivation towards learning outcomes of accounting students of class X of SMK Negeri 1 South Solok. The purpose of this study is to obtain empirical evidence about the influence of family environment and students motivation towards learning outcomes of accounting students of class X of SMK Negeri 1 South Solok.The method used in this research is descriptive and causative. This research is a saturated sampling or census, which used population sampled as many as 96 students out of a population of 96 students. Family environment data (X1) and motivation (X2) is obtained from the results of the questionnaire or questionnaires while accounting student learning outcomes data (Y) is obtained from the documentation of the value end of the semester. Analysis of the data used in this study is a descriptive analysis and inductive analysis which consists of classical assumption test, multiple regression analysis and hypothesis testing.The results showed that: 1. Family environment and a positive significant effect on learning outcomes of accounting students of class X of SMK Negeri 1 South Solok, 2. Motivation to study significant and positive impact on learning outcomes of accounting students of class X of SMK Negeri 1 South Solok, 3. Family environment and student motivation are jointly significant effect on learning outcomes of accounting students of class X of SMK Negeri 1 South Solok. Based on these results, it is suggested that students, parents, teachers and the school for more attention to the family environment and students motivation in the learning process in an attempt to further optimize the learning outcomes of accounting students of class X of SMK Negeri 1 South Solok. Keywords : Family Environment, Motivation, Learning Outcomes